INFLUENCE OF PROJECT BASED LEARNING (PjBL) MAKING BIOPLASTIC PRESERVANTS ON THE CREATIVE THINKING ABILITY OF STUDENTS IN THE MATERIAL OF BIODIVERSITY - Rahayu, Hanum Mukti (Universitas Negeri Medan, 2024)
From the interview with the biology teacher at Taman Mulia Private High School, it can be seen that the students' creative thinking skills have not been fully trained and no special assessment has been carried out. Overcoming these problems can be done by using a learning model that can encourage students and improve the ability of creative thinking skills by providing systematic projects. The purpose of this study was to determine how much influence the project-based learning (PjBL) model of making bioplastic preserves has on students' creative thinking skills in biodiversity material. This research method is a quasi-experimental design using the Nonequivalent Control Group Design. The sampling technique used simple random sampling with class X IIS 1 as the experimental class using the PjBL learning model for making bioplastic preserves and class X IIS 2 as the control class using the discovery learning model. The results of the effect size of 1.16 are in the large category and it is concluded that there is an influence on the creative thinking skills of students.